Mitochondrial Transplantation Attenuates Toxicity in Human Lymphocytes Caused by Clozapine and Risperidone - Abdollah Arjmand; Elaheh Azizi Javan; Jafar Shahraki; Rozhin Shaboustani; Enayatollah Seydi; Jalal Pourahmad (Tabriz University of Medical Sciences, 2023)
Background: Clozapine (CLZ) and risperidone (RIS) are drugs that have the ability to disrupt mitochondrial function. Also, these drugs increase the level of free radicals. Mitochondrial dysfunction plays a role in the etiology of various diseases. Replacement and treatment of defective mitochondria with healthy mitochondria have been considered. Mitochondrial therapy (mitotherapy) or exogenous mitochondria transplantation is a method that can be used to replace dysfunctional mitochondria with healthy mitochondria. This method can help in the treatment of diseases related to mitochondria. Methods: In this study, we investigated the transplantation effect of isolated lymphocyte mitochondria on the toxicity induced by CLZ and RIS on human blood lymphocytes. Lymphocytes were isolated using the Ficoll standard method. Mitochondria of human lymphocytes were used for mitotherapy. This study was conducted in 6 groups. After treatment, the level of reactive oxygen species (ROS), mitochondrial membrane potential (MMP), reduced glutathione (GSH) content, oxidized glutathione (GSSG) content, and adenosine triphosphate (ATP) content were evaluated. Results: Our data showed that CLZ (70 µm) and RIS (24 nM) caused cytotoxicity on human blood lymphocytes which are associated with ROS generation, collapse in MMP, decrease in GSH content, increase in GSSG content and change in ATP content. Mitochondria transplantation results showed that adding mitochondria of lymphocytes could protect the lymphocytes against the toxicity effects caused by CLZ and RIS. Furthermore, the results showed that pre-incubation with cytochalasin D considerably reserved the protective effects of mitotherapy in the human lymphocytes. Conclusion: We proposed that mitochondria transplantation or mitotherapy-affected blood lymphocytes with exogenous mitochondria could be used to treat CLZ and RIS-induced toxicity.